Shock Therapy : Psychology, Precarity, and Well-Being in Postsocialist Russia - Matza, Tomas Antero, 1972- (Book collections on Project MUSE., 2018)
After the collapse of the Soviet Union, Russia witnessed a dramatic increase in psychotherapeutic options, which promoted social connection while advancing new forms of capitalist subjectivity amid often-wrenching social and economic transformations. In this book, the author provides an ethnography of post-Soviet Saint Petersburg, following psychotherapists, psychologists, and their clients as they navigate the challenges of post-Soviet life. Juxtaposing personal growth and success seminars for elites with crisis counseling and remedial interventions for those on public assistance, the author shows how profound inequalities are emerging in contemporary Russia in increasingly intimate ways as matters of selfhood. Extending anthropologies of neoliberalism and care in new directions, the author offers a profound meditation on the interplay between ethics, therapy, and biopolitics, as well as a sensitive portrait of everyday caring practices in the face of the confounding promise of postsocialist democracy.